Resettlement and food security - Mueller, Valerie (International Food Policy Research Institute, 2013)
In 2011, the International Food Policy Research Institute (IFPRI) collected data for the final round of a panel survey to evaluate how the resettlement project affected the food security of program participants in the long term. Although programs like the CBRLDP appear in other African countries, few quantitative evaluations measure the short- or longterm impact of resettlement policies. However, great lessons can be learned from ongoing research on this matter in terms of the roles of land reform and migration in improving food security in sub-Saharan Africa.